Project Programme Monitoring Process: Methods, Tools, Techniques - Mateusz Trzeciak (Communications of International Proceedings, 2021)
The aim of the article is to verify the processes of monitoring and control of programme implementation and to indicate methods, techniques and tools increasing the effectiveness of this process. The research was carried out using an expert interview on a sample of 21 managers involved in the implementation of the programs. In the conducted research, attention was paid to: verification of programme areas subject to the monitoring and control process, empirical identification of the most frequently used methods, techniques and tools, as well as documents and procedures for the programme implementation monitoring and control process, as well as assessment of their effectiveness. As a result of the undertaken research effort, 12 areas of monitoring and control of the programme implementation were identified. Moreover, the analysis of the results clearly indicates the use of programme management system documents, however, the methods and techniques indicated by the experts are commonly known methods used in project management.
Keywords: Monitoring; Control; Programme Management; Methods